„Sprawozdanie z Logopedycznych Dni Uniwersytetu Śląskiego (2009–2011) - Rożek, Agnieszka (Logopedia Silesiana, 2012)
The report summarizing The Speech Therapy Days at the University of Silesia (2009–2011) ...